The Influence of Work Orientation and Work Motivation on Employee Performance at the Education Office of Central Tapanuli Regency - Deby Seftiani Tanjung; Azriadi Tanjung (Devitara Innovations, 2025)
This study aims to examine the influence of Work Orientation and Work Motivation on Employee Performance at the Department of Education, Tapanuli Tengah Regency. The research uses a quantitative method with a descriptive approach. The sample consisted of 56 employees of the Department of Education who were respondents through questionnaires. The results show a strong correlation between Work Orientation and Employee Performance (r = 0.776) and between Work Motivation and Employee Performance (r = 0.698). The coefficient of determination analysis indicates a value of 0.659, meaning that 65.9% of the variation in Employee Performance is simultaneously influenced by Work Orientation and Work Motivation, while the remaining 34.1% is affected by other factors not discussed in this study. Based on the t-test, Work Orientation (t_calculated = 5.164 > t_table = 1.674) and Work Motivation (t_calculated = 2.966 > t_table = 1.674) have a significant partial effect on Employee Performance. Furthermore, the F-test shows F_calculated = 51.246 > F_table = 3.17 with a significance of 0.000 < 0.05, indicating a significant simultaneous effect. Therefore, Work Orientation and Work Motivation positively affect Employee Performance at the Department of Education, Tapanuli Tengah Regency.